Do Higher Plasma Omega-3 Levels Predispose to Prostate Cancer? Results from the Intermountain INSPIRE Biobank Registry - Anderson, Jeffrey L; Le, Viet T; Jain, Mohit; McCubrey, Raymond O; Knight, Stacey; Bride, Daniel; Najhawan, Mahan; Dao, Khoi; Watrous, Jeramie D; Bair, Tami L; et al. (Cardiology and Cardiovascular Medicine, 2022)
Background: Omega-3 fatty acid supplements are widely used for cardiovascular (CV) prevention. However, a prominent report proposed that total and high-grade prostate cancer (PrCA) risk increased with increasing levels of docosahexaenoic acid (DHA) and trended to with eicosapentaenoic acid (EPA). Objective: Given public health implications, we prospectively tested this finding in the INSPIRE Registry. Methods: Plasma samples from men enrolled in the INSPIRE Registry who developed incident PrCA during follow-up were selected and matched 2:1 with men of similar age and entry date who were free of PrCA throughout follow-up. Plasma lipid fractions were analyzed by rapid throughput liquid chromatography-mass spectrometry. Omega-3 levels in the 2 groups were compared. Results: We identified samples from 87 men (age: 67.3 +/- 8.6 y) who developed PrCA (at 4.7 +/- 3.7 y) and matched them to 149 samples from control men (age: 66.2 +/- 8.6 y); follow-up averaged 10.1 +/- 3.8 y and 13.5 +/- 3.7 y, respectively. Entry levels of both EPA (p=0.012) and DHA (p=0.047) were significantly lower in PrCA patients than in controls. Levels also distinguished high-grade but not fatal PrCA. Conclusions: PrCA risk did not rise with increasing EPA and DHA levels; rather, findings suggest protective potential. These results are in keeping with the cancer safety of omega-3 supplements in recent randomized trials. However, our results go beyond supplementation to directly address the relationship of PrCA risk with circulating omega-3 levels, and they imply that supplementation may be based on potential CV benefits apart from concerns for PrCA risk.